GENDER PERFORMATIVITY IN BANG SALLEH/SALLY - Safrina Arifiani Felayati; Riefki Fajar Ganda Wiguna (Program Studi Pendidikan Bahasa Inggris Fakultas ilmu Budaya, 2023)
This article focuses on looking at gender performativity, a feminist theory approach put forward by Judith Butler on the character Bang Saleh or also called Bang Sally, in the Upin Ipin series. Upin Ipin is a popular children's animation series from Malaysia. In this animated series which is aimed at children and comes from a country with a majority Muslim population, it will seen how the character Bang Saleh/Bang Sally is presented. How is gender performativity in the character? The method used in this article is descriptive qualitative. In this study, it was found that the character Bang Sholeh/Sally showed performance with gender as a woman but was still within the corridors of law and religion in Malaysia. Hence, the character still had to perform as a man. Here it is seen that Bang Sholeh/Sally has a different gender identity.